P424 Uptake of a switching program for patients receiving intravenous infliximab and vedolizumab to subcutaneous preparations. (21st January 2022) - Alice, H; Gemma, B; Selinger, C P
Abstract: Background: Recent trials support the clinical efficacy and safety of subcutaneous (sc) biologic treatment for IBD maintenance therapy. Administration of sc injections could reduce the financial burden and time required to attend for infusions and allow IBD service providers to manage increasing clinical demand. We evaluated the uptake and rationale for choosing to switch from intravenous (iv) infusions to sc injections, including the impact of the Covid-19 pandemic on IBD service provision. Methods: All adult patients receiving standard dosing maintenance iv Infliximab or Vedolizumab therapy at a tertiary IBD centre were offered a switch to the respective sc formulations. We investigated the uptake of the switch from iv infusions to sc injections and utilised a standardised patient questionnaire to determine the rationale for switching to sc injections or not, and to identify areas for improvement in IBD service provision for the switching process. Results: In a cohort of, 232 eligible patients (258 total patients, 190 infliximab, 68 vedolizumab, 26 no longer eligible), 58% of patients receiving Infliximab and, 59% of patients chose to switch to sc treatment. Of the, 26 ineligible patients, 6 were switched to an intensified treatment schedule, 12 switched to a different biologic, 2 moved out of area, 5 had treatment stopped for clinical reasons and, 1 required operative treatment. There were no significant predictors for willingness to switch relating to patient age, sex, diagnosis, drug, line of treatment or duration of treatment (p>0.05). Early results from patient questionnaires (n=23) demonstrate that a decision to switch was not influenced by the impact on their mental health, Covid-19 risk, the impact on wider IBD service provision or financial savings, but, 70% of switchers did report that time savings influenced their decision. A minority of patients reported feeling pressured to switch (10% switchers and, 15% non-switchers) or had concerns about the safety (20% switchers, 0% non-switchers) and efficacy (40% switchers, 31% non-switchers) of sc injections. The majority of patients feel they were provided with sufficient Conclusion: Switch uptake rates were, 58% with, 90% of patients eligible to switch. We found no evidence that a decision to switch was influenced by age, sex, diagnosis, drug, line of treatment or duration of treatment. Non-switchers value face-to-face support at the IBD unit highly, and switchers value the time saved by administering injections at home. Switching to sc formulation not only provided patients with a choice of saving time usually required for iv administration but also reduced pressure in an overstretched IBD service.